Evolutionary analysis of galectins and identification of potential galectin-1 inhibitors: A computational approach - Vipperla Bhavaniprasad; Krishnan Anbarasu; Sivaraman Jayanthi (Bangladesh Pharmacological Society, 2014)
Galectins are a family of structurally related carbohydrate-binding proteins and some galectins play a major role in initiation, progression and dissemination of different types of tumors. Multiple sequence alignment was performed for 15 types of galectins and phylogenetic tree was constructed for studying evolutionary relationship. Among galectins, galectin-1 contributes to various events associated with cancer biology including tumor transformation, cell cycle regulation and apoptosis. Hence a rational computational approach was followed for the design of new class of glycol-mimetic inhibitors with high affinity and stability. Ten N-39-triazole analogs have been used for molecular docking with galectin-1. Based on docking studies, hexaconazole is identified as a potential inhibitor of galectin-1 for the inhibition of the tumor activity. The binding mechanism of hexaconazole to galectin-1 in the dynamics system was studied by 10 ns Molecular Dynamics simulation. Thus, our study favors more insight on hexaconazole as a promising inhibitor for galectin-1.